Water-soluble energy harvester as a promising power solution for temporary electronic implants - Zhang, Qian; Liang, Qijie; Rogers, John A. (APL materials, 2020)
Implantable biomedical devices are rapidly advancing for applications in in vivo monitoring and intervention for human health. A frontier for this area is in electronic implants that function in the body for some period of time matched to an intrinsic body process and then disappear naturally, thereby avoiding the need for surgical extraction. Continuous and stable power supply to these systems is of utmost importance for their practical implementation and function. Energy harvesters that are water soluble to biocompatible end products have great potential in this context. This article presents a comprehensive review of recent progress with a focus on materials selection, device integration, and function extension. We also discuss the challenges and possible future research opportunities associated with these technologies, with a focus on implantable biomedical devices.